PENGARUH PEMBERIAN POVIDONE IODINE DAN IODIUM TINCTURE SECARA TOPICAL TERHADAP FUNGSI KELENJAR TIROID - Kumorowulan, Suryati; Saidin, Sukati; Samsudin, M.; Kartono, Djoko (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2012)
ABSTRACT Background: Iodine Deficiency Disorder (IDD) is one of the main nutritional problems in Indonesia. The classic manifestation of IDD is goiter endemic and cretinism. Efforts have been conducted to eliminate IDD such as oral iodine supplementation and salt iodization. An alternative method that had been tried was through topical medication using iodine containing solution such as iodine tincture or povidone iodine. Both solutions were relatively cheap and almost available in every drug shop. This study was to explore the medicine to eliminate IDD which is rubbing self treatment and the danger of excessive iodine uptake is minimized. Objectives: The study was to investigate the effect of povidone iodine and iodine tincture by topical usage to the thyroid gland function. Methods: The study design was quasi experiment trial with pre- post design. Location of study was Srumbung and Dukun Subdistricts of Magelang District, Central Java. The subject was women of child bearing age (15–45 years) with visible goiter and normal thyroid stimulating hormone (TSH) level or hypothyroid. The subject were divided into two groups, each group consisted of 30 women of child bearing age. Group I was rubbed with povidone iodine on the neck every two days for 2 months and, group II was rubbed with iodine tincture with the same scheme as the first group. The level of TSH, free thyroxine (free T4) and urinary iodine excretion (UIE) were compared before and after intervention. Results: TSH level on povidone group (Group I) decrease from 3,6 μU/L (before) to 2,17 μU/L (after intervention). On tincture group also decrease from 2,7 μU/L to 1,42 μU/L. The median of free T4 on povidone group increase from 0,86 ng/dl (before) to 1,03 µg/dl (after intervention), whereas on tincture group the median of free T4 also increase with small value. The median of UIE on povidone group decrease from 383 μg/L (before) to 130 μg/L (after intervention), whereas on tincture group increase from 235 μg/L to 311 μg/L. The size of neck circle on povidone group showed that no significant difference between before and after intervention, whereas the tincture group had significant difference. Conclusions: The topical usage on thyroid gland of topical povidone iodine and iodine tincture improved TSH and free T4 levels. The treatment with iodine tincture decreased the size of goiter. [Penel Gizi Makan 2007, 30(1): 25-30] Keywords: povidone iodine, iodine tincture, TSH, free T4, UIE.